2014
DOI: 10.1093/europace/euu068
|View full text |Cite
|
Sign up to set email alerts
|

Contact force and force-time integral in atrial radiofrequency ablation predict transmurality of lesions

Abstract: Contact force and FTI during RF are correlated with TL. During RF delivery, a target FTI > 392 gs can be used as an endpoint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 17 publications
2
81
0
Order By: Relevance
“…It is possible that contact forcesensing catheters may lead to an improvement in outcomes. These catheters have already shown to be effective in improving lesion formation 35 and the outcomes of paroxysmal AF ablation. 36 Another explanation is that recurrence occurs because of progression of atrial disease, with development of further fibrosis and arrhythmogenic triggers leading to arrhythmia relapse requiring further ablation.…”
Section: Why Is Cfae Ablation Of No Benefit?mentioning
confidence: 99%
“…It is possible that contact forcesensing catheters may lead to an improvement in outcomes. These catheters have already shown to be effective in improving lesion formation 35 and the outcomes of paroxysmal AF ablation. 36 Another explanation is that recurrence occurs because of progression of atrial disease, with development of further fibrosis and arrhythmogenic triggers leading to arrhythmia relapse requiring further ablation.…”
Section: Why Is Cfae Ablation Of No Benefit?mentioning
confidence: 99%
“…Hence, an FTI Z400 g/s has been suggested as a surrogate end-point to predict the creation of transmural lesions in RF. 5,6 Booth et al recently highlighted the new real-time CF parameter of lesion size index (LSI). This novel parameter incorporates RF power, ablation duration, and CF in a dimensionless ratio independent of traditional parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Yet the dynamic range represents additional information on stability and the spectrum of forces that are applied during any given lesion to achieve the 400 g/s FTI target. 6,7 There is limited information on dynamic range; recently Kumar et al 10 showed a critical association between ventilation and ablation effectiveness; the index for dynamic ranges of force were noted to be strongly affected by respiration phase. This dynamic catheter behavior has implications for tip electrode stability, intermittent contact, and effectiveness of RF lesions.…”
Section: Discussionmentioning
confidence: 99%
“…An FTI Z400 g/s was previously suggested as an end point for effective lesions when contiguous lesion formation was possible. 6,7 We hypothesized that the dynamic range of forces may affect attempts to achieve 400 g/s and may be influenced by anatomic location and left atrial size, as this is a measure of stability of tissue contact. Higher peak forces have the potential for complication in addition to variable effectiveness.…”
Section: Introductionmentioning
confidence: 99%